Effect of Leptin Receptor Mutation on the Development of Chronic Bronchitis. Issue 4 (July 2013) - Wang, Boliang; Fu, Enqing; Cao, Yizhan; Zhong, Yuexia; Fu, Guoqiang; Tian, Xiaoxi; Li, Shanqu
To investigate the effect of serum leptin level and leptin receptor (Lepr) genetic mutation on chronic bronchitis, we measured the serum leptin levels of 236 patients with chronic bronchitis and 107 healthy controls by ELISA, the genotype distribution of Lepr gene containing Gln223Arg polymorphic sites by the polymerase chain reaction-restriction fragment length polymorphism (RFLP) method, the levels of inflammatory markers in serum, and the concentration of neutrophils. We found that the GG genotype distribution and G gene frequency of Lepr gene Gln223Arg site of the patient group were higher than that in the control group. The serum high-sensitivity C-reactive protein and neutrophil granulocyte levels of the patient group were higher than those of the control group. But the leptin concentrations of those with GG genotype were lower than those with AA+AG genotype ( P < .05). The mutation of Lepr gene Gln223Arg site may not directly influence the leptin level but could possibly advance the disease through inhibiting the biological effect of leptin.